Compositional Features of the Light Fraction from One/Two‐Step Effective Cascade Catalytic Hydroconversion of the Extraction Residue from Naomaohu Lignite. Issue 5 (2nd February 2022) - Yang, Zheng; Cong, Xing‐Shun; Xie, Heng‐Shen; Zhang, Min; Wei, Xian‐Yong
Abstract: Naomaohu lignite (NL) was extracted with isometric acetone/carbon disulfide mixed solvent under ultrasonic irradiation. The extraction residue (ER) was subjected to non‐catalytic hydroconversion (NCHC) and one/two‐step cascade catalytic hydroconversion (CHC) in n ‐hexane at 300 °C under 4 MPa of H2 over magnetic solid superacid (MSSA) and superbase (MSSB). The NCHC‐soluble portion from the NCHC (SPNCHC ) and CHC‐soluble portion from the one/two‐step cascade CHC (SPA, SPB, SPA‐B, and SPB‐A ) were analyzed with a gas chromatograph/ mass spectrometer (GC/MS). The results show that the yields of SPA and SPB are 18.65 % and 16.31 %, respectively, which are much higher than that of SPNCHC (1.26 %). According to the analysis with GC/MS, SPA and SPB are rich in phenol, dimethylnaphthalene, cresol, trimethylphenols, and xylenols, while alkanes are the predominant group component in the SPNCHC, indicating that MSSA selectively catalyzed the cleavage of Car −Calk and Calk −O bridged bonds, whereas MSSB tended to cleave Car −O and Calk −O bridged bonds connecting some aromatic rings in the ER. The yield of SPB‐A was as high as 11.07 % and SPA‐B was only 0.59 %. The results showed that more soluble species in the ER could be further released through the cascade CHC procedures. Benzyloxybenzene was used as a coal‐related model compound to probe the possible mechanisms of one/two‐step cascade CHC of the ER. Abstract : More organic matter in coal was converted into soluble species via one/two‐step cascade catalytic hydroconversion in n ‐hexane at 300 °C over magnetic solid superacid (MSSA) and superbase (MSSB). The results show that the yields of SPA and SPB are 18.65 % and 16.31 %, respectively, which are much higher than that of SPNCHC (1.26 %). The results proved that MSSA selectively catalyzed the cleavage of Car −Calk /Calk −O bridged bonds, whereas MSSB tended to cleave Car −O/Calk −O bridged bonds in coals.